Comparison of the effect of fennel and evening primrose oil on menopausal problems and hormonal levels: A randomized controlled trial - Fatemeh Ghavi; Fatemeh Shakeri; Heshmat Farahnaz; Somayeh Abdolahian (Wolters Kluwer Medknow Publications, 2023)
Background: Using natural oral supplements is one of the methods of complementary medicine that has been widely welcomed in the last decade Since studies have reported contradictory results for effectiveness of herbal medicines during menopause and no other more effective herbal medicine has been suggested yet, the researchers of this study decided to compare the fennel and Evening Primrose Oil (EPO) and their effect on menopause problems and sex hormones. Materials and Methods: The present study was a triple-blinded, controlled clinical trial with 125 participants randomly assigned to. An intervention group received fennel, another intervention group received evening primrose oil, and the placebo group received placebo twice daily for 8 weeks. Pre-intervention and post-intervention results were obtained using hormonal assay and the Menopause Rating Scale (MRS). Results: In this study, the mean follicle-stimulating hormone (FSH) and estradiol levels changed significantly in the fennel and EPO groups compared to placebo (p < 0.001). The difference in the mean FSH score between the fennel group and EPO group was not significant (p = 0.304), but the difference in the mean estradiol level between these groups was significant (p = 0.043). Moreover, there was a significant difference in the mean MRS score between the intervention groups before the intervention (p < 0.05). However, the difference in the mean MRS score between the fennel and EPO groups was not significant after the intervention (p = 0.322). Conclusions: Consumption of fennel and EPO can significantly change FSH, estradiol, and psychological menopausal symptoms in postmenopausal women.